Synthesis of novel 3-benzyl-2-phenyl-4(5H)-(substituted phenylhydrazino)-1, 3-oxazolidines and their antihyperglycemic activity - T Panneerselvam (Wolters Kluwer Medknow Publications, 2011)
A number of 3-benzyl-2-phenyl-4(5H)-(substituted phenylhydrazino)-1, 3-oxazolidines 6a-f derivatives were synthesized and their antihyperglycemic activity was evaluated by streptozotocin (STZ) and sucrose-loaded model. Many of oxazolidine derivatives as well as their corresponding substituted phenylhydrazine showed significant reduction in blood glucose level in STZ and sucrose-loaded rat models.